MicroRNA-21 deficiency suppresses prostate cancer progression through downregulation of the IRS1-SREBP-1 signaling pathway. (28th January 2022) - Kanagasabai, Thanigaivelan; Li, Guoliang; Shen, Tian Huai; Gladoun, Nataliya; Castillo-Martin, Mireia; Celada, Sherly I.; Xie, Yingqiu; Brown, Lakendria K.; Mark, Zaniya A.; Ochieng, Josiah; Ballard, Billy R.; Cordon-Cardo, Carlos; et al.
Abstract: Sterol regulatory element-binding protein 1 (SREBP-1), a master transcription factor in lipogenesis and lipid metabolism, is critical for disease progression and associated with poor outcomes in prostate cancer (PCa) patients. However, the mechanism of SREBP-1 regulation in PCa remains elusive. Here, we report that SREBP-1 is transcriptionally regulated by microRNA-21 (miR-21) in vitro in cultured cells and in vivo in mouse models. We observed aberrant upregulation of SREBP-1, fatty acid synthase (FASN) and acetyl-CoA carboxylase (ACC) in Pten/Trp53 double-null mouse embryonic fibroblasts (MEFs) and Pten/Trp53 double-null mutant mice. Strikingly, miR-21 loss significantly reduced cell proliferation and suppressed the prostate tumorigenesis of Pten/Trp53 mutant mice. Mechanistically, miR-21 inactivation decreased the levels of SREBP-1, FASN, and ACC in human PCa cells through downregulation of insulin receptor substrate 1 (IRS1)-mediated transcription and induction of cellular senescence. Conversely, miR-21 overexpression increased cell proliferation and migration; as well as the levels of IRS1, SREBP-1, FASN, and ACC in human PCa cells. Our findings reveal that miR-21 promotes PCa progression by activating the IRS1/SREBP-1 axis, and targeting miR-21/SREBP-1 signaling pathway can be a novel strategy for controlling PCa malignancy. Highlights: miR-21 deficiency suppresses prostate cancer progression in Pten/Trp53 double null mutant mice. miR-21 loss decreases the levels of SREBP-1, FASN and ACC through downregulation of IRS1-mediated transcription to reduce the proliferation of prostate cancer cells. Enforced overexpression of miR-21 increases levels of SREBP-1, FASN and ACC in human prostate cells. miR-21 inhibition decreases cell proliferation, the IRS1/SREBP-a signaling, and lipogenesis in prostate cancer cells.